Optimization of Probiotic Lactobacilli Production for In-Feed Supplementation to Feedlot Cattle - Cecilia Aristimuño Ficoseco; Flavia I. Mansilla; Graciela M. Vignolo; María E. Fátima Nader-Macías (Applied Microbiology, 2023)
The selection of probiotic bacteria based on their beneficial characteristics does not necessarily mean they can be later scaled up and used for technological applications and formula design. Three probiotic strains—Lactobacillus acidophilus CRL2074, Limosilactobacillus fermentum CRL2085, and Limosolactobacillus mucosae CRL2069, originally isolated from feedlot cattle feces—have demonstrated beneficial characteristics when used as in-feed probiotics. Therefore, the current study was conducted to develop a low-cost culture medium to optimize growth conditions to enhance biomass production. The study also sought to identify appropriate cryoprotective agents to sustain high functional cell numbers after freeze drying. A central composite design was applied to determine the optimal medium composition. This yielded a simplified, low-cost effective medium containing 3% molasses and industrial yeast extracts (0.5 to 2.5%) as carbon and nitrogen sources, which were added to a basal medium for each strain. Established production conditions at 37 °C, without agitation, and pH-controlled for the CRL2085 and CRL2069 strains, and free pH for the CRL2074 strain, allowed us to obtain biomass yields of 12.95, 18.20, and 12.25 g, respectively, at 24-h incubation, compared with the MRS medium. In addition, the cryoprotective effect of the selected agents was demonstrated to be strain-dependent. Thus, the highest viability (109–1010 CFU/g), stability during 30-d storage, and survival rate (88–99%) were achieved when 10% MSG (monosodium glutamate), sucrose + fructose + trehalose + WPC (whey protein concentrate) + 10% MSG, and 1.2% WPC + 10% trehalose, were used for freeze drying CRL2074, CRL2085, and CRL2069, respectively. Moreover, the probiotic strains retained their probiotic functionality when hydrophobic characteristics were evaluated. These results highlight the need to perform strain-specific evaluation of the critical factors involved in the large-scale production of probiotic lactobacilli to sustain viability and stability after the freeze drying and storage processes.